OBE-Oriented Teaching Material for Visual Media Development: Supporting the Internationalization of the Educational Technology Study Program - Dewi, Utari; Kristanto, Andi; Mubarok , Husni; Mulatu , Kifle Kassaw (Mitra Edukasi dan Publikasi, 2026)
Globalization in higher education demands innovative learning resources that support international collaboration and digital-based instruction. Responding to this need, this study develops Outcome-Based Education (OBE)-based visual media lesson plans to strengthen the internationalization of the Educational Technology Study Program. This study used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. A research and development approach was employed, involving expert validation and limited field trials with students in an Educational Technology program. The developed materials include OBE-aligned digital modules, instructional videos, worksheets, and project-based assessments integrated into an online learning management system. Validation results indicate a high level of feasibility in terms of content relevance, media quality, and visual design, while student trials suggest that the materials are practical and supportive of independent and collaborative learning. This study contributes a practical model for integrating OBE principles into digitally mediated courses that support international collaboration in higher education. The impact of this study lies in its contribution to improving students' global competencies, encouraging inter-institutional collaboration, and accelerating the internationalization of the Educational Technology Study Program. In addition, this study contributes to improving the quality of education in alignment with SDG 4 on Quality Education and strengthening internationalization efforts through global partnerships consistent with SDG 17 on Partnerships for the Goals.